Long-term adjustment of early-stage ovarian cancer survivors. Issue 6 (1st October 2008) - Matulonis, U. A.; Kornblith, A.; Lee, H.; Bryan, J.; Gibson, C.; Wells, C.; Lee, J.; Sullivan, L.; Penson, R.
Abstract : The objectives of this study were to describe the quality of life (QOL), consequences of treatment, complementary therapy use, and factors correlating with psychologic state in 58 survivors of early-stage ovarian cancer since little is known about the QOL of early-stage ovarian cancer survivors. Survivors were interviewed using standardized measures to assess physical, psychologic, social, and sexual functioning; impact of cancer on socioeconomic status; and complementary therapy use. Survivors reported good physical QOL scores and few unmet needs. However, menopausal symptoms and negative impact on sexuality were reported. Less than 10% of survivors reported either an interest in sex or were sexually active. Psychologic assessment yielded a subset of 26% of patients with scores suggestive of posttraumatic stress disorder (PTSD) and 40% of survivors scored below the norm on the Mental Health Inventory-17 Survey. One third of patients required treatment for family/personal problems and took antianxiety medications. About 56% of survivors reported fear of cancer recurrence and 59% reported anxiety when their CA125 is tested. Better mental health was significantly related to less fatigue (Functional Assessment of Cancer Therapy [FACT]—fatigue, r = 0.61, P < 0.0001), less pain (European Organisation for Research and Treatment of Cancer [EORTC], r = −0.54, P < 0.0001), fewer stressful life events (Life Event Scale, r = −0.44, P > 0.001), and greater social support (MOS Social Support Survey, r = 0.41, P < 0.01). Early-stage ovarian cancer survivors had few physical complaints and unmet needs, but psychologic distress was evident in a subset of survivors; the majority of survivors reported sexual dysfunction. These results indicate the need for intervention and improved distress screening in the early-stage ovarian cancer population.